First record of Desmodus rotundus in urban area from the city of Olinda, Pernambuco, Northeastern Brazil: a case report - Torres, Filipe Dantas; Valença, Carlos; Andrade Filho, Geraldo Vieira de (Revista do Instituto de Medicina Tropical de São Paulo, 2005)
The objective of this report is to describe the first record of Desmodus rotundus in urban area from the city of Olinda, Pernambuco State, Northeastern Brazil, and to draw attention to the possible risk of rabies transmission in this place. After the complaint of a dog owner who observed three bats attacking his dog, images registering attacks of D. rotundus were captured with a video camera. From 09:00 p.m. on 13 February 2004 to 04:00 a.m. of the next day, a high frequency of haematophagic activity and the presence of several bites on the dog's body were observed. This finding represents a serious risk to public health. Thus, it is necessary to further study the bat fauna, with special attention to their feeding behaviour in this place, in order to better know their biology and to adopt pertinent control measures. This is, to our knowledge, the first record of D. rotundus in urban area of Olinda.